Green Synthesis of Fe3O4 Nanoparticles Based on Natural Sand as Methylene Blue Degradation by Electrocoagulation Method - Fatimah, Siti; Juharni, Juharni; Wahyuni, Angraeni Sri Hanifa (POSITRON, 2023)
The green synthesis of Fe3O4 nanoparticles based on natural sand as a liquid waste degrader has been conducted. Fe3O4 powder was obtained by separating natural sand using a permanent magnet through the electrocoagulation method with Mn doping and AC composite. The 5 variations of Mn doping aimed to induce ferromagnetic properties and stabilize MnxFe3-xO4 particles as methylene blue degraders, while the AC composite aimed to enhance pollutant absorption. Characterization using Fourier Transform Infrared and X-Ray Diffraction analyzed the functional groups, nanostructure, and crystal size of MnxFe3-xO4 powder, showing that increasing the molarity of Mn doping strengthened functional group bonds and stabilized particle size up to 8.389 Å. The magnetic nanocomposite powder was applied to a methylene blue solution as a model for textile liquid waste. Ultraviolet Visible Light testing revealed decreased light absorbance in the surface state region and an energy bandgap widening of 5.25 eV. The larger energy bandgap indicated a lower refractive index, indicating the clarity of the resulting liquid. COD and BOD testing supported these findings, as samples with 0.3M and 0.7M doping showed a decrease in COD from 299.82 mg/L to 287.27 mg/L and a decrease in BOD from 127.08 mg/L to 115.16 mg/L. The characterization results demonstrated that the magnetic nanocomposite powder MnxFe3-xO4/AC effectively served as a methylene blue degrader. It transformed the sample colour into a clearer state and reduced pollutant levels, complying with the wastewater quality standard. This research offers an environmentally friendly solution for a cost-effective and efficient methylene blue degrader.